The influence of bone quality on the biomechanical behavior of full-arch implant-supported fixed prostheses - Faverani, Leonardo Perez [UNESP]; Ricardo Barao, Valentim Adelino; Ramalho-Ferreira, Gabriel [UNESP]; Delben, Juliana Aparecida [UNESP]; Ferreira, Mayara Barbosa [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Assunção, Wirley Goncalves [UNESP] (Elsevier B.V., 2014)
We evaluated the influence of bone tissue type on stress distribution in full-arch implant-supported fixed prostheses using a three-dimensional finite element analysis. Stresses in cortical and trabecular bones were also investigated. Edentulous mandible models with four implants inserted into the interforaminal region were constructed from different bone types: type 1 - compact bone; type 2 - compact bone surrounding dense trabecular bone; type 3 a thin layer of compact bone surrounding trabecular bone; and type 4 - low-quality trabecular bone. The mandible was restored with a full-arch implant-supported fixed prosthesis. A 100-N oblique load was applied to the left lower first molar of the prosthesis. The maximum (sigma max) and minimum (sigma min) principal stress values were determined. The sigma max in the type 4 cortical bone was 22.56% higher than that in the type 1 bone. The sigma min values in the cortical bone were similar among all the bone types. For the superstructure, increases of 9.04% in the sigma max and 11.74% in the sigma min in G4 (type 4 bone) compared with G1 (type 1 bone) were observed. For the implants, the highest stress values were located in G4, and the lowest values were observed in GI. In the trabecular bone, the highest stress was generated in G1 and G2. In conclusion, the more compact bones (types 1 and 2) are the most suitable for supporting full-arch implant-supported fixed prostheses, and poor bone quality may increase the risk of biological and mechanical failure. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Dental implants; Prostheses and implants; Finite element analysis